2012
DOI: 10.5539/sar.v1n1p48
|View full text |Cite
|
Sign up to set email alerts
|

Why and How to Make Plant Conservation Ecosystem-Based

Abstract: Compared to other groups of organisms, plants require distinctive approaches in their conservation because of their keystone roles in ecosystems and economies. The state of the whole plant cover of the Earth should be of concern to conservationists -for its capacity to ensure the survival of plant species, deliver ecosystem services (locally to globally) and provide produce from plants in ecologically sustainable ways. The primary targets of attention in ecosystem-based plant conservation are the relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This approach proposes that plants species must be conserved since they are key elements in the ecosystem, provide ecosystem services, and maintain complex biotic interactions in the natural communities. Under this approach all types of production have to be integrated, agriculture, livestock grazing, and all sustainable uses of the plants (Hamilton et al, 2012). In addition, the conservation of the plant species requires the prevention of land-degradation (Given, 1994, Hamilton et al, 2012, as well as it is necessary to control all those activities that cause reduction of the plant population size (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach proposes that plants species must be conserved since they are key elements in the ecosystem, provide ecosystem services, and maintain complex biotic interactions in the natural communities. Under this approach all types of production have to be integrated, agriculture, livestock grazing, and all sustainable uses of the plants (Hamilton et al, 2012). In addition, the conservation of the plant species requires the prevention of land-degradation (Given, 1994, Hamilton et al, 2012, as well as it is necessary to control all those activities that cause reduction of the plant population size (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Under this approach all types of production have to be integrated, agriculture, livestock grazing, and all sustainable uses of the plants (Hamilton et al, 2012). In addition, the conservation of the plant species requires the prevention of land-degradation (Given, 1994, Hamilton et al, 2012, as well as it is necessary to control all those activities that cause reduction of the plant population size (e.g. illegal harvesting, invasive plant species) and the genetic isolation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our analysis of the demographic history of D. sinensis indicated low nucleotide diversity and restricted gene flow between the WQM and EQM clades of the widely distributed populations of D. sinensis , thereby supporting our conclusion that the WQM and EQM populations are not interbreeding (Figure 4a). However, during field investigations, we found that illegal human activities (e.g., continuous harvesting, development of agriculture, the rise of tourism activities, low reproductive capacity, hydroelectric development, and other industrial actions) and genetic fragmentation have significantly depleted several natural populations of D. sinensis (Hamilton et al., 2012; Zhou et al., 2010). Due to the continuous decreases in the sizes of wild populations, it is necessary to protect the populations affected by human activities in order to save the natural ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that plant conservationists need social allies to boost their efforts – referring to elements of society whose primary interests in eco-civilisation construction are different, but whose efforts, if successful, will bring benefits to plant conservation too. Elsewhere, this expanded approach has been termed ecosystem-based plant conservation (EBPC) ( Hamilton, 2007 , Hamilton et al., 2012 ). Standard procedures still apply, but with more consideration given to who should be involved (not just to what needs to be done), taking into account the long-term sustainability of all ecological systems in which plants are significant components, and promoting conservation across the landscape.…”
Section: An Expanded Agenda Suggested For Plant Conservationistsmentioning
confidence: 99%
“…The complexity of ecosystems can make it difficult to know how to influence them effectively to meet particular goals. We suggest that an evidence-based approach is useful in plant conservation ( Hamilton, 2011 , Hamilton et al., 2012 ), just as it has proved in healthcare – similarly a science-influenced art dealing with complex systems with practical results required ( Sackett et al., 1996 ). An evidence-based approach involves periodic reviews of the evidence relating to success or failure in dealing with practical issues, followed by the formulation of recommendations on best practice.…”
Section: Suggested Principles Of Ecosystem-based Plant Conservationmentioning
confidence: 99%